THE SIGNIFICANCE OF IRFANI'S EPISTEMOLOGY TO THE PROBLEMATICS OF MODERN CIVILIZATION (Study on Seyyed Hossein Nasr's Epistemological Thought) - Siti Nurliani Nurliani (Universitas Islam Negeri Alauddin Makassar, 2023)
Abstract This article aims to discuss the significance of Irfani's Epistemology to the problems of Modern Civilization in the study of Sayyed Hussein Nasr's epistemological thinking, this research uses a qualitative research type with a philosophical approach and uses primary data sources in the form of Sayyed Hussein Nasr's original works and secondary data using books, scientific journals, research that discusses Sayyed Hussein Nasr's research both in Indonesian and foreign languages, and the analysis used is content analysis, through this research sacred knowledge or Scientia Sacra, As the basic concept of epistemology, Irfani Nasr seeks to restore metaphysics and spiritual traditions in human life. Responding to the problems of modernity, the most appropriate solution for Nasr is traditional knowledge contained in religions and spirituality as a treasure of eternal virtues. The concept of Irfani's epistemology is a form of traditional knowledge that can be a way for modern humans to treat the crisis of identity and the problems they experience. Keyword: Significance, Epistemology Irfani, Modern Civilization